1991
DOI: 10.1073/pnas.88.4.1575
|View full text |Cite
|
Sign up to set email alerts
|

AIDS epidemiology: inconsistencies with human immunodeficiency virus and with infectious disease.

Abstract: The newly defined syndrome AIDS includes 25 unrelated parasitic, neoplastic, and noninfectious indicator diseases. Based on epidemiological correlations, the syndrome is thought to be due to a new, sexually or parenterally transmitted retrovirus termed human immunodeficiency virus (HIV). The following epidemiological data conflict with this hypothesis. (i) Noncorrelations exist between HIV and AIDS; for example, the AIDS risks of infected subjects vary greater than 10-fold with their gender or country. Abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Declining CD4 counts in all the infected laboratory workers and outright AIDS in one demonstrate that this strain of HIV can indeed cause disease despite its long in vitro passage. Moreover, the development ofclinical features in the laboratory workers, in the absence of any other risk factors, clearly shows the Duesberg hypothesis, that HIV is not the cause of AIDS (25), to be untenable.…”
Section: Resultsmentioning
confidence: 98%
“…Declining CD4 counts in all the infected laboratory workers and outright AIDS in one demonstrate that this strain of HIV can indeed cause disease despite its long in vitro passage. Moreover, the development ofclinical features in the laboratory workers, in the absence of any other risk factors, clearly shows the Duesberg hypothesis, that HIV is not the cause of AIDS (25), to be untenable.…”
Section: Resultsmentioning
confidence: 98%
“…weeks or months, but AZT is now prescribed to healthy HIV-positives indefinitely, despite its known toxicity (Nussbaum, 1990;Volberding et al, 1990). Indeed, AZT has been shown to be toxic in HIV-positives and proposed as a possible cause of AIDS diseases since 1991 (Duesberg, 1991(Duesberg, , 1992c(Duesberg, , 1992a(Duesberg, , 1992b. Recently, the European 'Concorde tri-57 al' (Seligmann et al, 1994) and several other studies have shown that, contrary to earlier claims, AZT does not prevent AIDS (Oddone et al, 1993;Tokars et al, 1993;Lenderking et al, 1994;Lundgren et al, 1994).…”
Section: Mortality Of Hemophiliacs With and Without Hivmentioning
confidence: 67%
“…This hypothesis holds that AIDS in the major risk groups is caused by group-specific, recreational drugs and by anti-HIV therapy with cytocidal DNA chain terminators, like AZT, and is thus not infectious (Lauritsen & Wilson, 1986;Haverkos & Dougherty, 1988;Duesberg, 1991Duesberg, , 1992aOppenheimer, 1992). The drug-AIDS hypothesis was favored by many scientists, including some from the CDC, before the introduction of the HIV-AIDS hypothesis in 1984 (Marmor et al, 1982;Mathur-Wagh et al, 1984;Haverkos et al, 1985;Mathur-Wagh, Mildvan & Senie, 1985;Newell et al, 1985;Haverkos & Dougherty, 1988;Duesberg, 1992a;Oppenheimer, 1992).…”
mentioning
confidence: 99%
“…On the other hand, he also concedes that AIDS exists and offers causes [59], and seems unbothered by posing mutually exclusive arguments at the same time. In his earlier writings, he accepted that there is statistical association between HIV and AIDS (although he argued this was insufficient for causation) [60] and even considered the HIV-antibody test as useful surrogate to identify patients at risk of AIDS; [61] today, he denies that and argues that HIV is a passenger virus with no relationship whatsoever to AIDS [3]. In the same contradictory way, Duesberg has argued that HIV is not the cause of AIDS because ''in most individuals suffering from AIDS, no virus particles can be found anywhere in the body'' [62]; yet at about the same time that he published this, he was involved in a disagreement with other AIDS denialists who had challenged the very existence of HIV where he defended that ''HIV has been isolated by the most rigorous method science has to offer [63].'…”
Section: Does Hiv Cause Aids?mentioning
confidence: 99%